Gamification and Eco-Literacy: A Bibliometric Analysis of Research Trends - Paola Julie Aguilar-Cruz; Esther Julia Olaya-Marín (International Journal of Serious Games, 2025)
Environmental challenges demand innovative educational approaches to foster eco-literacy. Gamification, the use of game design elements in non-game contexts, has gained attention as a strategy to enhance engagement and learning. However, its role in eco-literacy education remains underexplored. The purpose of our bibliometric analysis was to investigate research trends, key contributions, and thematic developments in the application of gamification for promoting eco-literacy from 2018 to 2024. Using Scopus as the primary database, we implemented bibliometric methods, including co-authorship, keyword co-occurrence, and citation analysis, to map the scientific production in this interdisciplinary field. The findings revealed a growing academic interest in the topic, with an increasing number of publications and the emergence of dominant themes such as sustainability education, serious games, and digital learning tools. However, the results also highlight gaps in empirical studies assessing the effectiveness of gamification in enhancing eco-literacy outcomes. These insights contribute to a better understanding of how gamification can be implemented to strengthen eco-literacy and provide a foundation for future research in this field.